2013
DOI: 10.3109/01443615.2013.788622
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 for the diagnosis of ovarian torsion: A systematic review and meta-analysis

Abstract: Ovarian torsion may have significant fertility implications. Interleukin-6 is a pro-inflammatory cytokine, which may act as a helpful diagnostic test. Our objective was to investigate the accuracy of serum interleukin-6 in the diagnosis of ovarian torsion in women with ultrasonographic evidence of an ovarian cyst. An electronic search of published data, unpublished dissertations, theses and conference proceedings was performed. The systematic review involved observational studies. The studies had to provide da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…In the present study, white blood cell, neutrophil, and lymphocyte counts were all markedly higher in the torsion group than in the control group. Elevated serum concentrations of interleukin‐6 were previously shown to be associated with the occurrence of ovarian torsion . Cytokines might also function in the elevation of CA125 and the NLR …”
Section: Discussionmentioning
confidence: 94%
“…In the present study, white blood cell, neutrophil, and lymphocyte counts were all markedly higher in the torsion group than in the control group. Elevated serum concentrations of interleukin‐6 were previously shown to be associated with the occurrence of ovarian torsion . Cytokines might also function in the elevation of CA125 and the NLR …”
Section: Discussionmentioning
confidence: 94%
“…Serum D-dimer, ischemia-modified albumin, IL-6, IL-8, TNF-a, and E-selectin, have been investigated as serum markers in patients with ovarian torsion. Among these, elevated IL-6, D-dimer, and ischemia-modified albumin concentrations have been shown to be associated with ovarian torsion [2,[11][12][13][14][15]. Kart et al investigated the diagnostic value of plasma D-dimer level in an experimental rat ovarian torsion model and stated that D-dimer was well correlated with histopathological damage scores of ovarian injury and might be used as a plasma marker in early detection of ovarian torsion [14].…”
Section: Discussionmentioning
confidence: 96%
“…Christopoulos et al [11] investigated the accuracy of serum interleukin-6 in the diagnosis of ovarian torsion in women with ultrasonographic evidence of an ovarian cyst in a systematic review that involved observational studies. A total of three studies met their inclusion criteria [2,12,13].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that some serum biomarkers, such as serum d-dimer, IL-6, IL-8, tumor necrosis factor-alpha (TNF-α), heat shock protein 70, and ischemia-modified albumin, can play a role in the early detection of OT [ 7 27 28 29 ]. Kart et al [ 29 ] studied the diagnostic value of plasma d-dimer levels in an experimental rat OT model and found a significant correlation between plasma d-dimer levels and the histopathological damage scores of ovarian injuries.…”
Section: Discussionmentioning
confidence: 99%